Islamic Law Review of the Practice of Cemetery Land Transactions in Bandar Jaya Village, Rantau Rasau Subdistrict - Adrian Wiratama Saputra; Wargo; Wandi; Eti Fatiroh (Zabags International Journal of Islamic Studies, 2026)
The limitation of cemetery land has become an increasingly complex issue alongside population growth and the scarcity of public space, prompting the emergence of alternative practices in cemetery land management at the community level. This study aims to describe the practice of cemetery land transactions in Bandar Jaya Village, Rantau Rasau Subdistrict, and to analyze it from the perspective of Islamic law. The research employs a qualitative descriptive approach with a phenomenological strategy, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that the practice does not take the form of conventional buying and selling, but rather a collective contribution system that grants long-term usage rights to cemetery land within family structures, accompanied by fund management for social purposes and community investment. From the perspective of Islamic law, this practice tends to align with the principles of muamalah as long as it upholds justice, public benefit, and avoids prohibited elements, while also resembling the concepts of usufruct rights and waqf in the management of public assets. This study contributes to the enrichment of contemporary Islamic legal scholarship by offering a contextual analysis and proposing a sustainable, community-based model for cemetery land management oriented toward social welfare.